2019
DOI: 10.1371/journal.ppat.1008145
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei infection protects mice against malaria

Abstract: Sleeping sickness and malaria are parasitic diseases with overlapping geographical distributions in sub-Saharan Africa. We hypothesized that the immune response elicited by an infection with Trypanosoma brucei, the etiological agent of sleeping sickness, would inhibit a subsequent infection by Plasmodium, the malaria parasite, decreasing the severity of its associated pathology. To investigate this, we established a new co-infection model in which mice were initially infected with T. brucei, followed by admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 78 publications
(82 reference statements)
3
22
0
Order By: Relevance
“…These results indicate, however, that Anopheles mosquitoes could be exposed to Trypanosoma parasites when they feed on infected animals. Thus, as observed by Sanches-Vaz and others [12] in mice, this can conduct to a reduction of infection in Anopheles mosquitoes. Indeed, the absence of plasmodial infection in the sites where animals were found infected with T. vivax (sites with low malaria prevalence) and the presence of plasmodial infections in sites without trypanosome-infected animals, would be in favour of the involvement of trypanosomal infection in the plasmodial infection.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These results indicate, however, that Anopheles mosquitoes could be exposed to Trypanosoma parasites when they feed on infected animals. Thus, as observed by Sanches-Vaz and others [12] in mice, this can conduct to a reduction of infection in Anopheles mosquitoes. Indeed, the absence of plasmodial infection in the sites where animals were found infected with T. vivax (sites with low malaria prevalence) and the presence of plasmodial infections in sites without trypanosome-infected animals, would be in favour of the involvement of trypanosomal infection in the plasmodial infection.…”
Section: Discussionsupporting
confidence: 62%
“…In a recent study, Sanches-Vaz and others [12] showed through a co-infection model, that mice primarily infected with T. brucei, followed by the administration of P. berghei sporozoites, are protected from experimental cerebral malaria and presented increased host survival. In addition, subsequent infection of An.…”
Section: Introductionmentioning
confidence: 99%
“…brucei strongly impairs a secondary infection by P . berghei sporozoites in mice [ 27 ], similarly to what has been previously shown for the co-infection between Schistosoma and Plasmodium [ 28 ].…”
Section: Introductionsupporting
confidence: 62%
“…Experimental visceral leishmaniasis (VL) was also shown to confer enhanced protection against Streptococcus pneumoniae sepsis 6 . Similarly, in experimental models of malaria as a concurrent or superimposed infection, aggravating or protective responses were noticed 7 10 , suggestive of the role of immune dysregulation.…”
Section: Introductionmentioning
confidence: 92%